2018
DOI: 10.1371/journal.pone.0193819
|View full text |Cite
|
Sign up to set email alerts
|

Music@Home: A novel instrument to assess the home musical environment in the early years

Abstract: The majority of children under the age of 5 appear to show spontaneous enjoyment of singing, being exposed to music and interacting with musical instruments, but whether variations in engaging in such activities in the home could contribute to developmental outcomes is still largely unknown. Critically, researchers lack a comprehensive instrument with good psychometric properties to assess the home musical environment from infancy to the preschool years. To address this gap, this paper presents two studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 71 publications
4
84
0
1
Order By: Relevance
“…The present study revealed positive associations between the two subscales of the Gold-MSI (Musical Training and Active Engagement) and the general factor and most subscales of the Music@Home Infant and Preschool questionnaires. The results are in accordance with the results by Politimou and colleagues [34] regarding the Infant version and only partly in accordance regarding the Preschool version as in the English sample only Active Engagement but not Musical Training correlated with the Music@Home scores. Overall, it seems that musical engagement of the child is influenced by the general level of parents' musical activities and involvement with music, which is in accordance with previous research [44].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study revealed positive associations between the two subscales of the Gold-MSI (Musical Training and Active Engagement) and the general factor and most subscales of the Music@Home Infant and Preschool questionnaires. The results are in accordance with the results by Politimou and colleagues [34] regarding the Infant version and only partly in accordance regarding the Preschool version as in the English sample only Active Engagement but not Musical Training correlated with the Music@Home scores. Overall, it seems that musical engagement of the child is influenced by the general level of parents' musical activities and involvement with music, which is in accordance with previous research [44].…”
Section: Discussionsupporting
confidence: 90%
“…In order to explore whether the factor structure of the German Music@Home questionnaires was similar to the factor structure of the original English versions, we applied the same analysis to the German data as Politimou et al [34] applied to the English sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-parent of a 14-month-old child with typical development "Singing songs and playing musical games makes my daughter light up, even more so when those around her engage." -parent of a two-year-old child with Down syndrome Everyday parent-child musical experiences, like musical games and lullabies, are common in early childhood (Politimou et al, 2018). A growing body of research suggests that parent-child musical interactions may support dyadic attachment by promoting joint attention and emotional engagement (Creighton et al, 2013;de l'Etoile, 2006;O'Gorman, 2006;Perkins et al, 2018;Persico et al, 2017).…”
Section: Developmental Disabilitiesmentioning
confidence: 99%
“…The behavioral phenotypes and developmental delays associated with different disabilities may impact parent-child interactions and relationships (Spiker et al, 2002). However, despite the ubiquity of musical experiences in parent-child play (Levitin et al, 2004;Politimou et al, 2018), little is known about whether musical experiences differ for families of children with atypical development and whether or not musical experiences relate to parent-child attachment across families of children with different developmental profiles. In the current study, we examine parent-reported musical experiences of young children with and without developmental disabilities and their relationship with parentchild attachment.…”
Section: Developmental Disabilitiesmentioning
confidence: 99%